2015
DOI: 10.1021/jacs.5b10685
|View full text |Cite
|
Sign up to set email alerts
|

Optical Anisotropy of Black Phosphorus in the Visible Regime

Abstract: The striking in-plane anisotropy remains one of the most intriguing properties for the newly rediscovered black phosphorus (BP) 2D crystals. However, because of its rather low-energy band gap, the optical anisotropy of few-layer BP has been primarily investigated in the near-infrared (NIR) regime. Moreover, the essential physics that determine the intrinsic anisotropic optical property of few-layer BP, which is of great importance for practical applications in optical and optoelectronic devices, are still in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
246
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(276 citation statements)
references
References 45 publications
(81 reference statements)
10
246
0
1
Order By: Relevance
“…where c is the velocity of light, λ is the wavelength of the incident light and n is the linear refractive index, about 3.5 for BP [29]. The Im χ at 1030 nm decrease almost linearly with the linear transmittance when the size of nanosheets becomes smaller, as shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…where c is the velocity of light, λ is the wavelength of the incident light and n is the linear refractive index, about 3.5 for BP [29]. The Im χ at 1030 nm decrease almost linearly with the linear transmittance when the size of nanosheets becomes smaller, as shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies have revealed a range of intriguing anisotropic behaviors of BP in terms of its optical spectrum, Raman scattering, light absorption, photo-detection, and electrical conductivity. [27][28][29][30][31][32][33][34] While these properties reported in the literature have formed a valuable basis, many applications in the optical domain demand more information regarding the wave characteristics of the interacting light with the BP medium, specifically its phase. Moreover, the manipulation of the phase retardance of light in conjunction with interferometric techniques allows us to achieve optical contrast much stronger than an intensity measurement alone could 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 offer, as has been demonstrated extensively in optical metrology.…”
mentioning
confidence: 99%
“…However, this method is hard to give the BP thickness information directly without other characterization methods. In addition, BP samples with different layer numbers are found to present different colors under the illumination of halogen lamp in optical microscope . This thickness‐dependent color variation rule can be used to easily and quickly identify BP layer numbers but it has not been clarified yet.…”
mentioning
confidence: 99%
“…The red value reaches the maximum 255 from 59L to 138L, where the ranges of green and blue values are 128–184 and 13–76, respectively, which indicate that the colors of BP from 59L to 138L are between yellow and red. Refractive index of BP used here is from ZZ crystalline direction of few‐layer BP calculation results . According to the first‐principles simulation result, few‐layer black phosphorous strongly absorbs armchair‐polarized light (AC direction) and is transparent to zigzag‐polarized light (ZZ direction).…”
mentioning
confidence: 99%